Understanding digital industry : proceedings of the Conference on Managing Digital Industry, Technology and Entrepreneurship (CoMDITE 2019), July 10-11, 2019, Bandung, Indonesia /: proceedings of the Conference on Managing Digital Industry, Technology and Entrepreneurship (CoMDITE 2019), July 10-11, 2019, Bandung, Indonesia. (2020) - Unknown
No abstract available